Eutectic-directed self-templating synthesis of PtNi nanoporous nanowires with superior electrocatalytic performance towards the oxygen reduction reaction: experiment and DFT calculation. Issue 45 (6th November 2017) - Wang, Ying; Yin, Kuibo; Lv, Lanfen; Kou, Tianyi; Zhang, Chi; Zhang, Jie; Gao, Hui; Zhang, Zhonghua
Abstract : A bridge could be built between traditional eutectic alloys and advanced 1D nanowire materials through solidification/dealloying control. Abstract : One-dimensional (1D) nanostructures have been receiving significant attention due to their unique properties and potential applications. However, their low-cost, highly efficient synthesis remains a great challenge. Herein, we proposed a eutectic-directed self-templating strategy to synthesize PtNi nanoporous nanowires (NPNWs) through the combination of rapid solidification and dealloying. The eutectic-induced phase confinement and dealloying inheritance effect jointly favored the formation of PtNi NPNWs. The PtNi NPNWs exhibit superior electrocatalytic activity (5-fold enhancement in the specific activity) and enhanced durability towards oxygen reduction reaction, as benchmarked with commercial PtC. Moreover, the mechanisms for the activity enhancement have been rationalized on the basis of adsorption energy, d-band center, thermodynamics, and kinetics through density functional theory calculations.